Grodziska strefy lasostepu pontyjskiego we wczesnej epoce żelaza. Wstęp do dyskusji - Ignaczak, Marcin (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
The problem of the „giants’ strongholds” (of sizes often over 50 ha) situated in the early Iron Age in the Ukrainian forest steppe zone is the wealthy Russian and Ukrainian literature. Hitherto, many concepts explaining this phenomenon pursuant to politics (as a response to military threat) as well as to the economy (as a result of social organisation of local tribes) have been suggested. The main source of this discussion comes from the activities of a Polish-Ukrainian research expedition, – „Fortresses of Podolia”. It aims were to recognize and describe the history of strongholds forming the western Podolian settlement concentrating within the Ukrainian forest steppe. This programme is a derivate of the cooperation between the Institute of Archaeology of the Academy of Sciences of Ukraine and the Institute of Prehistory of the Adam Mickiewicz University in Poznañ2. Within the programme, researches of a Severinovka stronghold (Winnica district) were conducted in seasons 2009–2011 as a prologue of the project, as well as surface prospections in the area of western Podolia – mainly in the Winnica district. When interpreting the research results one has to examine the problems of strongholds of the „Scythian period”. In this article, which is an introduction to the discussion, the author would like to outline which processes may have led to fortifying the defensive settlements.